2013
DOI: 10.3998/gsf.12220332.0001.103
|View full text |Cite
|
Sign up to set email alerts
|

Global circuits of gender: women and high-tech work in India and the United States

Abstract: This article addresses the experiences of women in engineering and technology careers in an increasingly transnational era. It draws from an interview study, conducted during the early stages of the global high-tech industry, with over 180 women and men IT personnel in three organizational settings: a major Silicon Valley computer firm, its multinational subsidiary in India, and a local Indian IT firm. The IT industry, I find, has created new avenues of employment for women transnationally, but with variable t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 10 publications
0
13
0
Order By: Relevance
“…According to a study conducted in Indian, four technology‐hub cities found that girls are far less fearless of science and technology subjects than boys, and science subjects do not considered as unfeminine (Mukhopadhyay, 2005). Similarly, regarding the workforce gender parity in the high‐tech sector of India, an industry report of American Society of Engineering Education shows an increasing trend in the percent of women in the technology sector of India and reveals that the number of female engineers employed in India has surpassed the United States (Poster, 2013). Jonge (2014) also reports the higher proportion of female workforce and its positive effect on the representation of women on the boards for Indian high‐tech firms.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
“…According to a study conducted in Indian, four technology‐hub cities found that girls are far less fearless of science and technology subjects than boys, and science subjects do not considered as unfeminine (Mukhopadhyay, 2005). Similarly, regarding the workforce gender parity in the high‐tech sector of India, an industry report of American Society of Engineering Education shows an increasing trend in the percent of women in the technology sector of India and reveals that the number of female engineers employed in India has surpassed the United States (Poster, 2013). Jonge (2014) also reports the higher proportion of female workforce and its positive effect on the representation of women on the boards for Indian high‐tech firms.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
“…In this patriarchal society, women derive their roles mainly from family (Chowdhury, 2009) and are expected to behave in a gender congruent manner. In the public arena, women are often viewed as sexual objects and patriarchy is maintained either through sexual harassment (Chowdhury, 2009) or through limiting women's movement in the public space in the name of protecting women from dangerous environments (Poster, 2013).…”
Section: High-tech Careers and Women In South Asia: Bangladeshmentioning
confidence: 99%
“…While requirements for technical competence have been described as disqualifying women as ideal employees in the West, in India, women are not expected to be technically less competent than men (D'Mello 2006;Fuller and Narasimhan 2007;Poster 2013). Moreover, the new and emerging IT industry in India has been depicted as "de-gendered" and as providing Indian women with an opportunity to develop a "new identity" (Lau 2006).…”
Section: Gendered Work Ideals In It Companiesmentioning
confidence: 99%